The initial charge separation step in oxygenic photosynthesis - Yusuke Yoneda; Eric A. Arsenault; Shiun-Jr Yang; Kaydren Orcutt; Masakazu Iwai; Graham R. Fleming (Nature Communications, 2022)
The photosystem II reaction center (PSII-RC) is a model system to understand the initial steps of photosynthesis, but its excited state dynamics is difficult to disentangle with most spectroscopic methods. Here the authors perform a two-dimensional electronic-vibrational spectroscopic study of PSII-RC, providing detailed insight into such dynamics and into the mechanism of charge separation.